The Florida Automated Weather Network (FAWN): Ten Years of Providing Weather Information to Florida Growers - William Lusher; John Jackson; Kelly Morgan (EDIS)
SL-298, a 7-page illustrated fact sheet by William Lusher, John Jackson, and Kelly Morgan, describes the history, data collection and delivery, data access, management tools, impact, and recognitions of this state-wide network of automated weather sites that has been providing weather data in support of Florida agriculture. Published by the UF Department of Soil and Water Science, July 2009. Revised August 2009.